2020
DOI: 10.3389/fonc.2019.01470
|View full text |Cite
|
Sign up to set email alerts
|

Biological Determinants of Chemo-Radiotherapy Response in HPV-Negative Head and Neck Cancer: A Multicentric External Validation

Abstract: Purpose: Tumor markers that are related to hypoxia, proliferation, DNA damage repair and stem cell-ness, have a prognostic value in advanced stage HNSCC patients when assessed individually. Here we aimed to evaluate and validate this in a multifactorial context and assess interrelation and the combined role of these biological factors in determining chemo-radiotherapy response in HPV-negative advanced HNSCC. Methods: RNA sequencing data of pre-treatment biopsy material from 197 HPV-negative advanced stage HNSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 138 publications
(206 reference statements)
1
16
0
Order By: Relevance
“…The role of TNM, in contrast to EMT, in outcome is small and insignificant in both cohorts (Sup-Table S3 and S7), likely due to the advanced stage [4]. Multivariate analyses that include T-stage and N-stage provide increased HR and confirm the EMT association with OS and PFS in both cohorts (p < 0.05; Fig.…”
Section: A B Cmentioning
confidence: 71%
See 1 more Smart Citation
“…The role of TNM, in contrast to EMT, in outcome is small and insignificant in both cohorts (Sup-Table S3 and S7), likely due to the advanced stage [4]. Multivariate analyses that include T-stage and N-stage provide increased HR and confirm the EMT association with OS and PFS in both cohorts (p < 0.05; Fig.…”
Section: A B Cmentioning
confidence: 71%
“…Tumor biology studies revealed an important role for HPV and hypoxia in HNSCC [2][3][4]. HPV-positive oropharyngeal tumors represent a distinct subgroup of HNSCC that is associated with a good prognosis whereas tumor hypoxia markers reveal patients with a poor prognosis [5][6][7].…”
mentioning
confidence: 99%
“…Beyond or as a consequence of amino acid metabolism, SLC3A2/CD98 are involved in a wide range of functions relevant for cancer development and survival, such as mTOR pathway activation and autophagy [ 58 ], integrin signaling [ 59 ], immunity [ 60 ] and oxidative stress [ 58 , 61 ] and are negative prognostic factors in various cancers [ 62 , 63 ]. In HNSCC, SLC3A2/CD98 were described to mark tumor stem cell populations [ 64 ] and to confer a negative prognosis, which was completely restricted to HPV-positive tumors in one report [ 65 ] but primarily described for HPV-negative tumors in others [ 58 , 66 , 67 , 68 ]. In contrast to SLC3A2, there are no data regarding a possible prognostic role of leucine-rich PPR motif-containing protein (LRPPRC) in HNSCC.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have found that OSCC is a polygenic disease, and gene expression profiling technology has made highthroughput gene analysis possible (10)(11)(12)(13). Researchers can obtain the gene expression characteristics of a certain type of tumor by analyzing the gene expression profiles of tumor samples (14). Our previous research detected the expression of 22 candidate genes and 1 housekeeping gene in 120 OSCC tissue samples and 120 normal tissue samples at the mRNA level using real-time PCR (15).…”
Section: Introductionmentioning
confidence: 99%